Penyimpanan In Vitro Tanaman Obat Daun Dewa melalui Pertumbuhan Minimal - Endang G. Lestari; Ragapadmi Purnamaningsih (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumber Daya Genetik Pertanian, 2005)
Daun dewa (Gynura Procumbens) is a medicinal crop commonly used to remedy cancer, diabetes, and dermatitis. It has a bright prospect for future used. Plant preservations through tissue culture is done to anticipate an urgent need. An experiment was carried out to in vitro preservation of Daun Dewa by the minimum growth and regeneration to examine viability of the culture after the preservation. Terminal shoots (±1 cm) were cultured on a 1/2 MS basic medium + paclobutrazol (0, 1, 2, 3, and 4 mg/l) or ABA (1, 2, and 5 mg/l). The trial was arranged in a, completely randomized with 10 replications. The results showed a three-month preservation of the culture on a medium containing ABA inhibited proliferation and expansion of the plant shoots. Increasing ABA concentrations up to 5 mg/l, according to the shoot-growth inhibition, resulted in the height of 0.6 cm. After three month preservation, the shoots were able to produce roots. After 12 month preservation, the optimum capacity of growth inhibition was shown on 1/2 MS medium + ABA (1, 3, and 5 mg/l). The application of paclobutrazol (1, 2, 3, and 4 mg/l) in the medium produced low multiplication level of shoots, the length of the shoots remains higher than those on 1/2 MS medium without paclobutrazol. Seven months after preservation, viability of the plants was still high when cultured on MS medium + 2 mg/l BA combined with paclobutrazol and ABA as previously given. In addition, the rooted culture could be directly acclimatized in the glasshouse. The lowest number of shoot and shortest shoot after 12 month preservation period was found on the medium containing 5 mg/l ABA and 4 mg/l paclobutrazol, this treatment produced two shoots of 4 cm long. The best medium for the explant regeneration after 7 month preservation was MS + 2 mg/l BA. The plant shoots produced roots directly after they were acclimatized in the glasshouse.